PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. BAKRIE PIPE INDUSTRIES BEKASI - Imam Wibowo; Rusma Patriansyah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2016)
The purpose of this research is to know the information about relationship between independent variables which are training (X1) and motivation (X2) with dependent variable which is employee performance (Y) of PT. Bakrie Pipe Industries Bekasi, both simultaneously and partially. Data collected from 78 employee of PT. Bakrie Pipe Industries Operating Division randomly using Slovin formula. Then all data was analyzed by using regression and statistical analysis using F-statistic to know the influence of independent variable simultaneously and t-statistic to know the influence of independent variable partially with using SPSS Ver. 22 software. The results of this research shown that: 1). Simultaneously, training and motivation have positive influence and significant to employee performance of PT. Bakrie Pipe Industries Bekasi. 2). Partially, training has positive influence and significant to employee performance of PT. Bakrie Pipe Industries Bekasi. 3). Partially, motivation has positive influence and significant to employee performance of PT. Bakrie Pipe Industries Bekasi.